1998
DOI: 10.1111/j.1469-7793.1998.145bi.x
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic regulation of calcium‐activated potassium current in cultured rabbit pigmented ciliary epithelial cells

Abstract: 1. The effects of adrenergic agonists on K¤ currents were studied in cultured rabbit pigmented ciliary epithelial (PCE) cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The absence of such a component in the total I Tpn-Q suggests that adrenaline and Tpn-Q inhibit the same current, which was not detected by the total I Tpn-Q measurement since it had been already inhibited by adrenaline. While BK channels are stimulated by α1-and β-adrenergic pathway activation in other tissues [7,32,47], they are inhibited by somatostatin in the HIT insulinoma cells [44]. Since the α 2 -adrenoceptor-mediated inhibitory action of adrenaline predominates in β-cells, it appears reasonable that adrenaline leads to BK inhibition in these cells.…”
Section: Discussionmentioning
confidence: 96%
“…The absence of such a component in the total I Tpn-Q suggests that adrenaline and Tpn-Q inhibit the same current, which was not detected by the total I Tpn-Q measurement since it had been already inhibited by adrenaline. While BK channels are stimulated by α1-and β-adrenergic pathway activation in other tissues [7,32,47], they are inhibited by somatostatin in the HIT insulinoma cells [44]. Since the α 2 -adrenoceptor-mediated inhibitory action of adrenaline predominates in β-cells, it appears reasonable that adrenaline leads to BK inhibition in these cells.…”
Section: Discussionmentioning
confidence: 96%
“…(1980) demonstrated that prazosin lowered IOP in the rabbit eye by decreasing the rate of aqueous humor production. Ryan et al . (1998) suggested that potassium channels coupled to alpha‐1 ARs might modulate fluid secretion by the ciliary epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies have revealed that alpha‐1 ARs are involved in the regulation of intraocular pressure (IOP) in rabbits and monkeys (Kiuchi et al ., 1992; Nishimura et al ., 1993; Wang et al ., 1997; Zhan et al ., 1998; Okada & Gregory, 2001). Moreover, alpha‐1 ARs have been found to regulate cellular functions in cultured endothelial cells from various ocular regions in several species (Walkenbach et al ., 1992; Moroi‐Fetters et al ., 1995; Ryan et al ., 1998). However, which subtype(s) of alpha‐1 AR is involved in the ocular functions remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of K þ channels and membrane hyperpolarization by the Ca 2þ -or cAMP-mediated secretagogue is reported in many cases of exocrine cells [7,23,24]. The role of the BK type of K(Ca) channel in luminal K þ secretion or in electrogenic Cl À secretion has been suggested in various exocrine cells, including the pigmented ciliary epithelium of rabbit [25], the pancreatic acinar cells of pig [26], human vas deferens epithelial cells [27], and the acinus of the mouse salivary gland [28]. The IK type of K(Ca) channel also plays an important role in the electrolyte-fluid secretion of the pancreatic acini of some species [24] and of the colonic crypt [23,29].…”
Section: Role Of K þ Channels In the Secretory Epitheliummentioning
confidence: 99%
“…In many kinds of exocrine epithelia, muscarinic stimulation is linked to PLC/IP 3 signaling pathways and releases stored Ca 2þ . The subsequent increase in [Ca 2þ ] i regulates many kinds of Ca 2þ -activated ion channels, including Ca 2þ -activated Cl À channels [24] and K(Ca) channels [23][24][25][26][27][28]. The prostate is no exception to the concept that the male reproductive tract receives abundant innervation from both the sympathetic and parasympathetic divisions.…”
Section: Role Of Muscarinic Receptors and Purinoceptors In Rpse Cellsmentioning
confidence: 99%